Analysis of Sudoku Compilation Algorithms: Understanding Number Concepts in Students Special Needs at Extraordinary School - Sakdiyah, Halimatus; Sujiwo, Dimas Andhita Cahyo; Panglipur, Indah Rahayu (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
Children with autism spectrum disorder (ASD) often have difficulty understanding abstract concepts such as numbers, requiring interactive and concrete learning media. This study analyzed the systematic thinking, or algorithmic processes, of children with autism spectrum disorder as they solved complex Sudoku puzzles. Using a qualitative descriptive approach, three students with different levels of functioning at extraordinary school C TPA Jember were observed. This study used a 4x4 dot Sudoku game with pictures as a more easily understood learning medium. Data analysis was conducted by comparing data from the work results, visual documentation, and field notes. Data analysis used an interactive qualitative approach based on Miles and Huberman. The results indicated that picture Sudoku can support the algorithmic thinking of children with ASD, although the level of success varies based on individual abilities. Students with lower functional levels require full guidance, but students with higher functional levels lack sufficient independence and problem-solving skills. The conclusion of this study is that picture Sudoku has proven to be an effective tool for improving the algorithmic thinking of children with autism, highlighting the importance of concrete and adaptive learning media.